Destination choice of Chinese long-haul outbound tourists and market segmentation - Li, Chunxiao; McCabe, Scott; Ye, Chen (Taylor & Francis, 2017)
China is an important emerging generator of outbound international tourism. Recent studies have investigated trip characteristics and specific behaviours of Chinese travellers but have focused on intraregional patterns of actual tourists and short-haul destinations. By utilizing both qualitative and quantitative methods, this study uncovers the attributes considered important by potential long-haul tourists during destination selection. Based on these attributes, the market segmentation is further explored through the combination of conjoint analysis and cluster analysis. The interview data reveal that cost, visa restrictions, time schedule of the package, whether the destination is famous and the availability of opportunities to shop for branded goods are important choice criteria. The cluster analysis suggests that the Chinese long-haul outbound market can be divided into three subgroups which are labelled as “Journey beginner”, “Conspicuous Consumer” and “Prestige pursuer”.